(untitled) (Fiep Bulletin - online, 2012)
The chronic nonspecific low back pain (CNL) has high incidence and may interfere with the mobility of the lumbar spine and level of inability of individuals. A major cause may be the tension of the muscles and fascia. Among the many features for its treatment there is the manual therapy, which, through myofascial techniques, stretching and normalizes shortened tissues and, consequently, can improve mobility and reduce abnormal tension in the body. The aim of this study was to assess the influence of myofascial techniques on the level of inability, decreased pain and increased range of motion of the lumbar spine in employees of the State University of West Paraná with chronic nonspecific low back pain. The sample consisted of 15 patients with CNL, sedentary, aged 20 to 55 years. Were not included individuals with low back pain, whose medical history suggested no mechanical etiology or nervous system involvement and practicing regular physical activity. The patients were treated for 10 sessions, with a protocol which consisted of myofascial manipulation techniques, for three weekly sessions. In the first and last session was applied the Roland-Morris questionnaire and were made evaluations of the mobility of the lumbar spine (Shober test and modified Shober test). During all sessions were seen at the beginning and the end of the intervention, the amount of present pain (visual analog scale). There were statistically significant differences in flexion (<0.0001), extension (0.0046), Roland-Morris questionnaire (<0.0001) and pain (p <0.0001). Was concluded that the protocol with myofascial techniques can decrease the levels of pain, increase range of motion of the lumbar spine and lower levels of inability in patients with CNL.